Basic Anthropometric Measures in Acute Myocardial Infarction Patients and Individually Sex- and Age-Matched Controls from the General Population - Göran Nilsson; Pär Hedberg; Jerzy Leppert; Andreas Rosenblad; John Ohrvik (Hindawi Limited, 2018)
We compared weight, height, waist and hip circumferences (hip), body mass index (BMI), and waist-to-hip ratio in acute myocardial infarction (MI) patients and individually sex- and age-matched control subjects from the general population in the catchment area of the patients and predicted the risk of MI status by these basic anthropometric measures. The study cohort comprised 748 patients ≤80 years of age with acute MI from a major Swedish cardiac center and their individually sex- and age-matched controls. The analyses were stratified for sex and age (≤65/≥66 years). Risk of MI was assessed by conditional logistic regression. A narrow hip in men ≥66 years was the single strongest risk factor of MI among the anthropometric measures. The combination of hip and weight was particularly efficient in discriminating men ≥66 years with MI from their controls (area under the receiver operating characteristic (AUROC) curve = 0.82). In men ≤65 years, the best combination was hip, BMI, and height (AUROC = 0.79). In women ≥66 years, the best discriminatory model contained only waist-to-hip ratio (AUROC = 0.67), whereas in women ≤65 years, the best combination was hip and BMI (AUROC = 0.68). A narrow hip reasonably reflects small gluteal muscles. This finding might suggest an association between MI and sarcopenia, possibly related to deficiencies in physical activity and nutrition.